Peran Daya Tarik dan Keahlian Streamer terhadap Niat Pembelian melalui Flow Experience - Fernando Justin Herman; Rita Amelinda (Jurnal Ekonomi, 2025)
This study aims to analyze the influence of Streamer Attractiveness and Streamer Expertise on Purchase Intention, mediated by Flow Experience, in the context of Live Shopping on TikTok among Gen Z in West Jakarta. Streamer Attractiveness creates emotional and visual appeal, keeping the audience engaged during Live Shopping sessions. Meanwhile, Streamer Expertise provides valid and convincing product information, building trust in the product recommendations to meet audience needs. The study collected data from 120 Gen Z respondents residing in West Jakarta. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the WarpPLS 8.0 software. The findings revealed that Streamer Attractiveness and Streamer Expertise significantly influence Flow Experience and Purchase Intention. Additionally, Flow Experience mediates the relationship between Streamer Attractiveness and Streamer Expertise on Purchase Intention. These insights offer theoretical contributions to digital marketing literature and practical implications for businesses to optimize Live Shopping strategies.